An Evaluation of the Management of Asymptomatic Catheter-Associated Bacteriuria and Candiduria at The Ottawa Hospital - Dawn M Dalen; Rosemary K Zvonar; Peter G Jessamine (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Asymptomatic catheter-associated urinary tract infections (CAUTIs) are common in hospitalized patients. They are associated with a low incidence of sequelae and morbidity, and in most patients resolve spontaneously on removal of the catheter. As a result, it is not recommended that asymptomatic catheter-associated bacteriuria or candiduria be treated with antimicrobial agents while the catheter remains in place because it may lead to the evolution of resistant flora.